Evaluation of heavy metal pollution in the Zayandeh-Rud River as the only permanent river in the central plateau of Iran - Karimian, Sana; Chamani, Atefeh; Shams, Masoumeh (Environmental monitoring and assessment, 2020)
Zayandeh-Rud River is the only permanent river in the central plateau of Iran. This river has been subject to an extensive discharge of wastewater and effluents from several point and nonpoint pollution sources. Accordingly, sediment quality of Zayandeh-Rud River in Varzaneh region, were studied. Algae and the sediment were sampled through 3 replications at 6 stations in the downstream after crossing through the Isfahan city and reaching Gavkhuni international wetland. Chlorophyll content and As, Pb, and Cd concentrations were measured in each sample Cladophora sp. and Oscillatoria sp. were identified using standard identification keys. The mean concentrations of metals in all stations exceeded background levels. Mean concentration of arsenic (162.9 mg/kg) in the sediment is about 31 times more than the ISQG standard (5.9 mg/kg) and considerably higher than the similar studies in Iran and other regions of the world. The mean concentration of As in algae samples is higher than the most polluted areas of the world. The mean concentration of Pb in the sediment (19.69 mg/kg) is lower than the ISQGs standard (35 mg/kg) and most of the studied river in north of Iran such as Chalous, Baboul-Rud, Gorgan-Rud (North), Khiav (North West), and Anzali wetland. The mean concentration of Cd in the sediment (2.11 mg/kg) is significantly higher than ISQG standard (0.6 mg/kg and some north highly polluted wetlands of Iran such as Anzali. There is a significant positive correlation between the mean concentrations of As and Pb in the sediment and Cladophora sp. tissue, and a negative one between the mean concentration of Pb in the sediment and chlorophyll b/a. There are significant negative correlations between the mean concentration of As in the sediment and chlorophyll a, and the total chlorophyll concentration in Oscillatoria sp . The results of Muller index indicate that the concentrations of Pb, Cd, and As in all stations occur in the Unpolluted, Moderate/Heavy, and Heavy/Extreme groups, respectively. Degree of contamination and modified degree of contamination show very high degree of pollution in the studied area. RI in all the stations showed very high ecological risk. The bioaccumulation factor for all metals in both algae is less than one. So, these two species may not be described as heavy metal accumulators. This study is an alarm for the Zayandeh-Rud River as the most important freshwater source for the Iranian Plateau. Graphical abstract